The Middle East between Eras of Globalization: A Comparative Perspective - Shecter, Relli (Jama'a: an Interdisciplinary Journal of Middle East Studies, 2009)
This short essay offers a new perspective on the past and present of the Middle East based on a comparison between two eras of globalization; the first ending during World War I, and he second one of the present day. In both periods, the region integrated rapidly into the world economy. The comparison this allows for an analysis of the different contexts, both local and international, in which globalization took place.